A Comparison of Applicants' and Incumbents' Mean Scores on Health Constructs and Personality Constructs. A Follow‐up Study of Military Recruits in a Selection Setting. (June 2015) - Bäccman, Charlotte; Sjöberg, Lennart; Almqvist, Kjerstin
<x xml:space="preserve">Abstract</x> This study investigated the change in means on both personality constructs and the more infrequently studied, health constructs, as a possible effect of self‐enhancement in a real selection setting. The participants (N = 202) were assessed first as applicants, and later as incumbents. The result revealed that, while all the means for personality constructs changed across situations, the effect sizes on the health constructs were stronger. The analysis also revealed that it was twice as likely for the incumbents to confirm having experienced previous traumatic/stressful events compared with applicants. Implications for the observed changes on both personality and health constructs in military selection setting are discussed.